Práctica deportiva en los niños con síndrome de down en la Institución Educativa Especializada Un Nuevo Amanecer de la ciudad de Babahoyo - Sandoya Vera, Jeancarlos Agustin (2023)
The present case study is related to sports practice in children with Down syndrome, so that the students of this institution have a better lifestyle and obtain more activity in their body and in some way they could avoid the chances of problems. motor skills and low muscle tone. Recreational sports help children with Down syndrome do it for pleasure and fun, without having any purpose of winning, they can practice them just to enjoy the sport. This helps children have a distraction and spend their free time in activities that are beneficial for their health.